Refractory Status Epilepticus Responsive to Electroacupuncture at Shuigou Acupoint: A Case Report - Yuan, Fang; Lu, Aili; Wu, Shibiao; Wang, Lixin (Frontiers in Neurology, 2020)
Refractory status epilepticus (RSE) is a critical and intractable neurological emergency. Around 55% of RSE episodes still persist despite high dose of continuous infusion of anesthetics. It’s a clinical urgency and challenge to search for novel alternative treatments to control RSE as soon as possible. Here, we reported a case of RSE in a 67-year-old woman with varicella-zoster virus encephalitis. She had persistent nonconvulsive SE despite the continuous infusion of midazolam. On the basis of fundamental treatments, she was given electroacupuncture at Shuigou acupoint for ten mins. An immediate EEG suppression was seen after the electroacupuncture treatment and lasted for nine mins, and lasting epileptic discharges (> 10s) and clinical seizures were not observed any more. Midazolam was withdrawn gradually 24 hours later. This case report may bring an alternative treatment for RSE.